“It helps me to stay on the right path, rather than give in”: Mixed-method process evaluation of the ImpulsePal app-based intervention for weight management - Samantha B van Beurden; Colin J Greaves; Charles Abraham; Natalia S Lawrence; Jane R Smith (Digital Health, 2023)
Background Empirical research indicates that impulsive processes that operate below conscious monitoring can undermine peoples’ attempts to change behaviour patterns, especially those that have become habitual. This may, therefore, be a serious challenge for those trying to lose weight. A novel smartphone app-based intervention (ImpulsePal) offers practical strategies to manage impulsive urges to facilitate reductions in the consumption of energy-dense processed food and overeating. Aim This process evaluation of ImpulsePal aimed to explore what was delivered/received and used, mechanisms of action, and potential contextual factors impacting intervention engagement and outcomes. Methods A mixed-methods process evaluation, with composite analysis of the quantitative (app usage statistics) and qualitative data (semi-structured interviews), was conducted alongside a feasibility randomised controlled trial with individuals with a body mass index of at least 25 kg/m 2 who wanted to lose weight. Results Of 58 participants receiving ImpulsePal, 56 had successfully shared app usage statistics, and 36 (62%) were interviewed. Although usage statistics indicated reductions in the use of some features, interviews indicated that participants were still using app-recommended strategies without requiring them to open ImpulsPal. Overall, interviews highlighted that participants valued having access to in-the-moment support, felt more aware of their own eating behaviour and influences on it, and felt an increased ability to avoid and reconceptualise, in-the-moment temptations. Conclusion This process evaluation offers support for a logic model suggesting that impulse management, using ImpulsePal, can promote healthier eating among those motivated to lose weight. It also highlights the necessity of using multimodal methods to explore the delivery and use of digital interventions.